Re-examining Head Coverings in Nigerian Christianity: Biblical Interpretation, Cultural Tradition and Contemporary Significance - Jezreel Smith Mietuade (CV Projurnal Mitra Publikasi, 2025)
A theological and socio-cultural analysis of head covering in contemporary Nigerian Christianity, examining its biblical foundation, historical development, and present significance. The diversity of interpretation and practice across Nigerian denominations reflects an ongoing tension between tradition, biblical interpretation, and cultural adaptation. The study critically evaluates three interpretive perspectives on 1 Corinthians 11:2–16: head covering as a universal Christian command, as a culturally shaped instruction from Paul, or as a symbolic practice related to order and gender relations in worship. Methodologically, the study adopts a qualitative approach, combining exegetical analysis of Pauline texts, historical-theological review from the early church to modern Christianity, and socio-cultural interpretation within the Nigerian church context. Findings show that head covering in Paul’s teaching is rooted in first-century honor-shame culture and worship practice, while its historical reception reveals wide differences in interpretation and application. In Nigeria, these differences are shaped by denominational traditions, cultural ideas of modesty, and changing gender roles in church and society. The study argues that strict universal application may ignore cultural meaning, while purely relative interpretation may weaken theological depth. It concludes that head covering is best understood as a culturally shaped theological symbol expressing order, honor, and reverence in worship rather than a fixed transcultural command, and calls for a balanced interpretation combining biblical faithfulness with cultural awareness in contemporary Nigerian Christianity.